2015
DOI: 10.1111/1462-2920.12852
|View full text |Cite
|
Sign up to set email alerts
|

Development, diet and dynamism: longitudinal and cross‐sectional predictors of gut microbial communities in wild baboons

Abstract: Summary Gut bacterial communities play essential roles in host biology, but to date we lack information on the forces that shape gut microbiota between hosts and over time in natural populations. Understanding these forces in wild primates provides a valuable comparative context that enriches scientific perspectives on human gut microbiota. To this end, we tested predictors of gut microbial composition in a well-studied population of wild baboons. Using cross-sectional and longitudinal samples collected over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 68 publications
14
80
3
Order By: Relevance
“…Finally, we found only weak shifts in gut microbiota composition within the flock over the nonbreeding season, and individual stints underwent large, seemingly random, fluctuations in their gut microbiota composition and diversity, demonstrating a remarkably changeable microbiota within individuals even during sedentary periods. Such dramatic shifts have also been found in other wild species such as anolis lizards (Ren, Kahrl, Wu, & Cox, ) and baboons (Ren, Grieneisen, Alberts, Archie, & Wu, ), suggesting microbial fluctuations in community composition, potentially in response to short‐term shifts in host diet or physiology, may be the norm in wild animals, independent of being sedentary or migratory. However, our findings suggest these changes are likely to be due to short‐term shifts in diet or physiology, rather than exposure to altered environmental microbiota.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Finally, we found only weak shifts in gut microbiota composition within the flock over the nonbreeding season, and individual stints underwent large, seemingly random, fluctuations in their gut microbiota composition and diversity, demonstrating a remarkably changeable microbiota within individuals even during sedentary periods. Such dramatic shifts have also been found in other wild species such as anolis lizards (Ren, Kahrl, Wu, & Cox, ) and baboons (Ren, Grieneisen, Alberts, Archie, & Wu, ), suggesting microbial fluctuations in community composition, potentially in response to short‐term shifts in host diet or physiology, may be the norm in wild animals, independent of being sedentary or migratory. However, our findings suggest these changes are likely to be due to short‐term shifts in diet or physiology, rather than exposure to altered environmental microbiota.…”
Section: Discussionmentioning
confidence: 64%
“…Such dramatic shifts have also been found in other wild species such as anolis lizards (Ren, Kahrl, Wu, & Cox, 2016) and baboons (Ren, Grieneisen, Alberts, Archie, & Wu, 2016), suggesting microbial fluctuations in community composition, potentially in response to short-term shifts in host diet or physiology, may be the norm in wild animals, independent of being sedentary or migratory. However, our findings suggest these changes are likely to be due to short-term shifts in diet or physiology, rather than exposure to altered environmental microbiota.…”
Section: Discussionmentioning
confidence: 79%
“…In similar fashion, pronounced temporal variation in the microbiota of individuals was also observed in faecal samples from wild baboons (Ren et al . ). In Burmese pythons, bacterial diversity and community composition in the gut changed rapidly and dramatically within hours to days of feeding, and these changes were primarily due to shifts in the abundance of endogenous gut bacteria, rather than the introduction of new bacteria from the rodent meal (Costello et al .…”
Section: Discussionmentioning
confidence: 97%
“…The associations between age and sex and the gut microbiome have been described for a handful of NHP species: black howler monkeys ( A. pigra ) (Amato et al, , ), yellow baboons ( P. cynocephalus ) (Ren, Grieneisen, Alberts, Archie, & Wu, ), ring‐tailed lemurs ( L. catta ) (Bennett et al, ), rufous mouse lemurs ( M. rufus ) (Aivelo, Laakkonen, & Jernvall, ), captive lemurs ( V. variegata , L. catta , P. coquereli ) (McKenney, Rodrigo, & Yoder, ), and chimpanzees ( P. t. schweinfurthii ) (Degnan et al, ). In general, some of these studies have suggested that individuals in early stages of development and females exhibit gut microbiome patterns associated with higher metabolic demands (e.g., higher abundance of fermentative taxa) during juvenile development, female pregnancy, and lactation (Amato et al, ; Mallott, Amato, Garber, & Malhi, ).…”
Section: Introductionmentioning
confidence: 99%